A strategy for removal of foreign body in mandible with navigation system. Issue 7 (July 2015) - Li, P.; Li, Z.; Tian, W.; Tang, W.
Abstract Navigation surgery in the mandible has rarely been reported because of the complexities of navigating a mobile structure. In this article, we present a simple and novel strategy for removal of a foreign body in the mandible using a navigation system. A female diagnosed with a foreign body in the left mandible underwent navigation surgery using a BrainLAB system. We used a special open splint fabricated with acrylic resin to successfully perform the mandibular navigation. This strategy may be appropriate for many types of mandibular navigation surgery.